Cultural Intelligence Profiles of Guidance and Counseling Teachers - Latif, Suciani; Aswar, Aswar; Amirullah, M; Harum, Akhmad (IAIN Kudus, 2023)
Cultural Intelligence Profiles of Guidance and Counseling Teachers. Cultural bias is one of the inhibiting factors in guidance and counselling, so the process of guidance and counselling in schools is often less than optimal. One of these problems is identified by the low cultural intelligence of guidance and counselling teachers. This study aims to investigate the level of cultural intelligence of guidance and counselling teachers in providing services to students at school . The survey method with descriptive statistical analysis was used to obtain an overview of the level of cultural intelligence of guidance and counselling teachers, which was strengthened through the interpretation of the results of interviews with informants. Respondents in this study amounted to 81 people, who came from high school, and vocational junior high school levels in South Sulawesi. The results showed that the level of cultural intelligence of guidance and counseling teachers at the high school level was 19.5%; SMK was 21.88%, and SMP was 53.57%, which does not consider the cultural diversity of students (such as ethnicity, religion, language, socio-economic status, gender, etc.) in providing guidance and counseling services to students. It has implications for the inability of guidance and counseling teachers to develop multicultural-based service programs, at SMA 14.29%; SMK at 15,63%; and SMP at 21.43%. In general, this study illustrates the low cultural intelligence possessed by guidance and counseling teachers, so that a follow-up effort is in the form of development and training modules to enhance teacher guidance and counseling cultural intelligence.Keywords: Profile, Cultural Intelligence, Guidance and Counseling Teacher